In vitro gametogenesis and reproductive cloning: Can we allow one while banning the other?. (5th September 2018) - Segers, Seppe; Pennings, Guido; Dondorp, Wybo; de Wert, Guido; Mertes, Heidi
Abstract: In vitro gametogenesis (IVG) is believed to be the next big breakthrough in reproductive medicine. The prima facie acceptance of this possible future technology is notable when compared to the general prohibition on human reproductive cloning. After all, if safety is the main reason for not allowing reproductive cloning, one might expect a similar conclusion for the reproductive application of IVG, since both technologies hold considerable and comparable risks. However, safety concerns may be overcome, and are presumably not the sole reason why cloning is being condemned. We therefore assess the non‐safety arguments against reproductive cloning, yet most of these can also be held against IVG. The few arguments that cannot be used against IVG are defective. We conclude from this that it will be hard to defend a ban on reproductive cloning while accepting the reproductive use of IVG.